2017
DOI: 10.1177/0886260517692336
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Violence Socialization and Approval of Intimate Partner Violence Among University Students in Kosovo

Abstract: Intimate partner violence (IPV) among university students is a prevalent problem in many countries; however, it is not currently recognized in Kosovo as a social issue in terms of research, prevention, and intervention. The aim of this article was to examine the relationship between violence socialization experiences, approval of violence, and IPV perpetration/victimization among university students in Kosovo. The questionnaires were administrated to a convenience sample of 700 students of University of Prisht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
1
14
0
3
Order By: Relevance
“…In a review of the adolescent dating abuse, however, it was reported that young women tended to maintain a good relationship with their partners by controlling their own desires and longings [18]. According to a cross-sectional study of 700 college students, as people viewed the relationship as important and strived to maintain it, violent situations that might occur between the two would be more tolerated [24]. It is also reported to be highly likely that even unwanted sexual intercourse would be tolerated to maintain the relationship in a qualitative study of young adults [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the adolescent dating abuse, however, it was reported that young women tended to maintain a good relationship with their partners by controlling their own desires and longings [18]. According to a cross-sectional study of 700 college students, as people viewed the relationship as important and strived to maintain it, violent situations that might occur between the two would be more tolerated [24]. It is also reported to be highly likely that even unwanted sexual intercourse would be tolerated to maintain the relationship in a qualitative study of young adults [25].…”
Section: Discussionmentioning
confidence: 99%
“…In studies investigating young individuals' attitudes towards dating violence, it was similarly stated that males supported dating violence more compared to females. 16,30 Besides, it could be inferred from this finding that, in the traditional structure of the Turkish society where the patriarchal order defines gender roles, males are more prone to violence, and they accept violence as a symbol of manhood.…”
Section: Discussionmentioning
confidence: 92%
“…A nivel internacional, los estudios sobre violencia de pareja en universitarios(as) son cuantitativos en su mayoría y predominan los que indagan sobre las percepciones y las actitudes que en torno a este fenómeno desarrollan los(as) jóvenes (Aguanunu, 2014;Davidson, Lozano y Cole, 2015;Ferrer et al, 2006;Kelmendi y Baumgartner, 2017;Li, Sun y Button, 2017;Nordin, 2019;Páramo y Arrigoni, 2018;Pugh, Li y Sun, 2018;Spencer, Morgan y Bridges, 2017;Wang, 2019;Wilson y Smirles, 2020). Investigar sobre percepciones y actitudes frente a la violencia de pareja en gran medida tiene la intención de identificar a los predictores de las conductas violentas.…”
Section: Introductionunclassified